1989
DOI: 10.1002/ajpa.1330320507
|View full text |Cite
|
Sign up to set email alerts
|

Provisioning and the study of free-ranging primates: History, effects, and prospects

Abstract: Since the first field primate studies there has been debate over whether or not provisioning as an aid to observation of free-ranging groups alters behavior and population processes t o the extent that those studies are not indicative of the animals' natural lives. If they are not, a significant amount of long-term data on several species of primates would be rendered irrelevant to analysis of natural population processes, and to the pool of knowledge of behavior and social groups on which a picture of histori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 104 publications
3
45
0
Order By: Relevance
“…A second pattern of early weaning was associated with high resource availability and good maternal condition. Comparisons of provisioned and non-provisioned populations have revealed that provisioned females exhibit shorter interbirth intervals and lactational periods, live longer, and exhibit higher infant survival rates than non-provisioned conspecifics (see reviews in Paul and Kuester, 1988;Asquith, 1989;Hendrickx and Dukelow, 1995). Additionally, there are reports that females with access to higher quality (but nonprovisioned) diets (e.g., vervet monkeys: Hauser and Fairbanks, 1988) and those with high dominance rank (e.g., yellow baboons, Papio hamadryas cynocephalus: Altmann and Samuels, 1992) invest less time and energy in offspring than females in relatively moderate condition and/or access to resources of moderate quality.…”
Section: Discussionmentioning
confidence: 99%
“…A second pattern of early weaning was associated with high resource availability and good maternal condition. Comparisons of provisioned and non-provisioned populations have revealed that provisioned females exhibit shorter interbirth intervals and lactational periods, live longer, and exhibit higher infant survival rates than non-provisioned conspecifics (see reviews in Paul and Kuester, 1988;Asquith, 1989;Hendrickx and Dukelow, 1995). Additionally, there are reports that females with access to higher quality (but nonprovisioned) diets (e.g., vervet monkeys: Hauser and Fairbanks, 1988) and those with high dominance rank (e.g., yellow baboons, Papio hamadryas cynocephalus: Altmann and Samuels, 1992) invest less time and energy in offspring than females in relatively moderate condition and/or access to resources of moderate quality.…”
Section: Discussionmentioning
confidence: 99%
“…Many primates close to humans systematically consume anthropogenic foods including garbage, offerings, and food provisioned by local people and tourists [Asquith, 1989;Wheatley et al, 1996;Fuentes et al, 2011;Malaivijitnond et al, 2011;Aggimarangsee, 2013]. The inclusion of human food in the diet can have significant effects on activity budgets [Brennan et al, 1985;Fa, 1986;Altmann and Muruthi, 1988;O'Leary and Fa, 1993;Saj et al, 1999;Sha and Hanya, 2013a].…”
Section: Introductionmentioning
confidence: 99%
“…Such studies can suggest ways of recon ciling conservation and control of the ani mals. Habituation of primates by regular pro visioning or food handouts can have major effects on ecology and behaviour [4,5]. It can also affect human perceptions of and behav iours towards the primates concerned [6],…”
Section: Introductionmentioning
confidence: 99%